OPTIMALISASI PENERIMAAN PAJAK DAERAH DALAM MASA COVID-19 TERHADAP PENDAPATAN ASLI DAERAH KOTA PEKANBARU - Habib Habib (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2023)
ABSTRACT The decline in local tax revenues, especially hotel and restaurant taxes, experienced the deepest decline. The hotel tax that is usually collected is Rp. 4 billion in a month, now only Rp. 200 million. The decline also occurred in restaurant taxes. Restaurant taxes that normally collect Rp 11 billion per month now only collect Rp 2 billion. The data above shows that there have been some declines in several tax items, but the Pekanbaru City tax target has remained stable in the first two semesters of 2020, local taxes collected in the period January to June 8 amounted to Rp. 198 billion. Meanwhile, tax revenue at Bapenda Pekanbaru in the second quarter of 2020 reached IDR 256 billion. Based on data from the Pekanbaru City Regional Revenue Agency (BAPENDA), the total amount of Pekanbaru City taxes with achievements for 2020 is 537.8 billion. Even though it is still in Covid-19 conditions, Pekanbaru City Tax is still better than 2018. This study aims to determine the optimization of local tax revenue during the Covid-19 period for local revenue in Pekanbaru City. This study used descriptive qualitative method. Data collection techniques using observation, interviews and documentation using the snowball method as a source of information. The results of this study indicate that from several sources of PAD, the main concern is tax revenue. In this tax revenue, the realized value achieved increased before the pandemic period, and remained stable during the pandemic. From this basis it can be seen that the regional tax sector has quite an influence on Pekanbaru City's PAD even in the Covid-19 situation..